S42. NEUROANATOMY OF EMOTIONAL PROCESSING AND IMPACT ON CLINICAL OUTCOMES IN SUBJECTS AT HIGH RISK OF PSYCHOSIS. (9th April 2019) - Modinos, Gemma; Kempton, Matthew; Tognin, Stefania; Calem, Maria; Porffy, Lilla; Antoniades, Mathilde; Azis, Matilda; Valmaggia, Lucia; McGuire, Philip; ,
Abstract: Background: The development of adverse clinical outcomes in psychosis has been associated with behavioral and neuroanatomical changes related to emotional processing (Aleman & Kahn, 2005; Philips & Seidman, 2008). However, the relationship between emotional processing deficits and neuroanatomy in subjects at clinical high risk of psychosis (CHR), and their relationship to longitudinal outcomes, remains unclear. The primary aim of the present study was to investigate the association between facial emotional recognition and grey matter volume (GMV) in a large cohort of CHR individuals compared to healthy controls, and their relationship with subsequent clinical outcomes. Methods: Structural imaging scans at 3T and a computer-based measure of emotional processing (Degraded Facial Affect Recognition task, DFAR), were collected at baseline from 53 healthy controls (mean age: 23.3 SD ± 3.9; 52.8% male) and 213 CHR subjects (mean age: 22.9 SD ± 4.7; 50.7% male) participating in the multi-centre EU-GEI study (data pooled from 9 sites). CHR subjects were then clinically monitored for 12 months and clinical outcomes were assessed in terms of transition/non-transition to psychosis (CAARMS criteria) and the level of overall functioning (Global Assessment of Function scale; GAF). Structural images were preprocessed with voxel-based morphometry in SPM12. DFAR performance (total, happy, angry, fear and anger) was analyzed with repeated measures ANOVA at baseline (HC/CHR as between-group factor and DFAR as within-subject factor, adjusted for age, gender, IQ and site); and with binary logistic regression at the 12-month follow-up point (adjusting for the same variables). One-way ANOVAs in SPM12 were specified to examine interactions between group status (HC/CHR, CHR-T/CHR-NT, CHR-GO/CHR/PO) and DFAR performance (total, happy, angry, fear and anger), adjusting for the same variables. Statistical inferences were made at p<.05 after voxel-wise FWE correction within four pre-defined anatomical regions of interest (ROI: amygdala, hippocampus, insula, anterior cingulate cortex/medial prefrontal cortex -ACC/MPFC-). Results: At baseline, DFAR performance did not differ between HC and CHR groups and was not significantly associated with GMV in our ROIs. At the 12-month follow-up point, 39 CHR subjects showed good overall functioning (GAF≥65), whereas 93 CHR subjects had a poor functional outcome (GAF score<65); 44 CHR subjects developed a psychotic disorder and 169 did not. Compared to subjects with a good functional outcome, CHR subjects with poor overall functioning showed exacerbated recognition of angry facial emotion (p=.030), decreased GMV in ACC and hippocampus (both p=.033 FWE), and a significantly different (inverse) association between angry facial emotion recognition and hippocampal volume compared to CHR subjects with good functioning (p=.037 FWE). CHR subjects who developed psychosis did not show significant differences in DFAR performance or significant associations between DFAR and GMV compared with CHR subjects who did not become psychotic. Discussion: These findings indicate that adverse global functional outcomes in people at CHR of psychosis (but not transition to psychosis) are associated with baseline deficits in the recognition of angry facial emotion, which are in turn directly related to hippocampal volume decreases compared to CHR subjects with good functional outcomes. This has implications not only for stratification of CHR subjects according to baseline behavioral and volumetric characteristics, but also suggest potential preventative avenues for poorer outcomes focused on social cognitive and emotional processes.